Food Security and HIV/AIDS: An Integrated Response to the Dual Epidemics of Hunger and HIV/AIDS in Africa - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2006)
Project Concern International (PCI) and partners hosted the Africa Forum from May 8 - 12, 2006, in Lusaka, Zambia. The Forum provided an excellent opportunity for local NGOs and international public health and development organizations to share experience